2010
DOI: 10.2355/isijinternational.50.1941
|View full text |Cite
|
Sign up to set email alerts
|

Solidified Structure Control of Metallic Materials by Static High Magnetic Fields

Abstract: Recently, the studies on the effects of high magnetic fields on solidification processes have been paid much attention both from the fundamental and applied points of view. With the aid of the enhanced Lorentz force and magnetization effect caused by the remarkably increased magnetic field intensity, several interesting phenomena, such as the control of fluid flow and particle migration in a melt, crystal orientation, and phase alignment, have been obtained. Moreover, the magnetic force induced by the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In early research, it has been found that migration and separation of primary phase during solidification of a liquid metal can be induced corresponding to the magnetic Faraday force, for example, primary Si in Al–Si alloys Segregation of primary phase had been observed and gradient metallic materials could be prepared by using the magnetic Faraday force . When solid particles/inclusion exist in the liquid metal, electromagnetic Archimedes force is applied to the solid particles: fnormalPEA=32σnormalMσnormalP2σnormalM+σnormalPJ×B where fnormalPEA is the force density, σM and σnormalP are the electrical conductivity of the liquid metal and the non‐conductive inclusion, respectively.…”
Section: Electromagnetic Field Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In early research, it has been found that migration and separation of primary phase during solidification of a liquid metal can be induced corresponding to the magnetic Faraday force, for example, primary Si in Al–Si alloys Segregation of primary phase had been observed and gradient metallic materials could be prepared by using the magnetic Faraday force . When solid particles/inclusion exist in the liquid metal, electromagnetic Archimedes force is applied to the solid particles: fnormalPEA=32σnormalMσnormalP2σnormalM+σnormalPJ×B where fnormalPEA is the force density, σM and σnormalP are the electrical conductivity of the liquid metal and the non‐conductive inclusion, respectively.…”
Section: Electromagnetic Field Effectsmentioning
confidence: 99%
“…The application of some EM fields in industry has been well established, ranging from EMBR, induction heating, cold crucible etc . One of the important aspects for the engineering of electromagnetic fields is for clean metals production.…”
Section: Industrial Application Potential – a Specific Case Analysis mentioning
confidence: 99%
“…[3] In recent years, high magnetic fields have been applied in materials processing, especially in solidification, as a non-contact method to more precisely control the material microstructure. [4][5][6][7] It has been found that the microstructure is strongly dependent on the migration behaviors of solutes and particles (or particle-like phases), so a comprehensive understanding of the evolution of the migration behaviors of solutes and particles during solidification processes in high magnetic fields is essential for the prediction and control of the final microstructures and properties of materials. [8] Several studies have investigated the effects of high magnetic fields on migrations of solutes and particles in alloy melts during solidification [9][10][11] and some research has specifically been directed to the effects of high-gradient magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Focused efforts on exploring magnetic field effects have suggested that magnetic fields could change fluid flow, phase equilibrium, and crystal orientation in terms of the Lorentz and magnetic force and magnetization [1]. There then arises the possibility of in situ controlling the solidification process by magnetic fields.…”
Section: Introductionmentioning
confidence: 99%